Urinary 3-hydroxypropyl mercapturic acid (3-HPMA) concentrations in dogs with acute spinal cord injury due to intervertebral disc herniation. (January 2017) - Sangster, A.M.; Zheng, L.; Bentley, R.T.; Shi, R.; Packer, R.A.
Highlights: Urinary 3-hydroxypropyl mercapturic acid (3-HPMA) is a metabolite of acrolein. In dogs with intervertebral disc herniation, urinary 3-HPMA concentrations were higher than in control dogs. Urinary 3-HPMA concentrations were not correlated with the severity of canine acute spinal cord injury (ASCI). Urinary 3-HPMA concentrations of intact dogs were higher than that of neutered dogs. 3-HPMA is a potential biomarker in canine acute spinal cord injury (ASCI). Abstract: The aim of this study was to investigate urinary 3-hydroxypropyl mercapturic acid (3-HPMA), a metabolite of acrolein, as a novel biomarker in acute spinal cord injury (ASCI) due to intervertebral disc herniation in dogs. Urine from 10 client-owned dogs with ASCI collected at presentation and 10 control dogs was analyzed for 3-HPMA. The median urinary 3-HPMA concentration in ASCI dogs was significantly higher than in control dogs, but was not correlated with the severity of ASCI. The median urinary 3-HPMA concentration in intact dogs was higher than in neutered dogs. Higher urinary 3-HPMA concentrations in dogs after ASCI support a role for acrolein, a cytotoxic by-product of lipid peroxidation, in canine ASCI. Urinary 3-HPMA could be used as a biomarker in future clinical trials to measure the effect of therapeutic intervention of reducing acrolein after ASCI.